IMMUNITY STATE IN THE OFFSPRING OF RATS EXPOSED ANTIGENS TOXOPLASMA GONDII - T. F. Sokolova; D. G. Novikov; A. V. Indutny; N. Ye. Turok; G. N. Velichko (Бюллетень сибирской медицины)
Today the questions about possibility of development disturbances in the immune system of the fetus and the newborn in chronic toxoplasmosis are poorly understood. Aim of research: to detect immunological disturbances in the offspring of rats which have been administered antigens T. gondii.Two series of experiments was performed. In these experiments white female Wistar rats in the III trimester of pregnancy have been administered corpuscular antigen T. gondii. The 60 days-old offspring of these rats have been included in study group of 137 animals. CD3+ cells count was performed in peripherical blood and standard suspension of splenocytesrats offspring. Peripherical blood cells count was performed in the blood of the rats offspring. In the second experiment rats offspring have been administered sheep erythrocytes in 5 days, before euthanasia. In spleen of this rats antigen-produced cells was counted.In control group was included 118 animals, which was born from white female Wistar rats have been administered 0,9% NaCl solution. CD3+ cells was detected in Cytomics FC500 flow cytometry analyzer (Beckman Coulter,USA) by use rats origne-specifed monoclonal antibodies Anti-Rat CD3-FITC (Beckman Coulter,USA). Hematological parameters was assessed by use hematological analyzer Excell-22 (USA).We observed, that CD3+ lymphocytes and antigen-produced cells was decreased in test group (degress of decrease CD3+ cells was 17,2%; р = 0,003 in spleen vs. control group, degress of decrease antigen-produced cells was 27,3%; р = 0,03 vs. control group). Number of leukocytes was increased in in test group (34,5%; р = 0,009 vs. control group). Power and strength correlation pleiades between studied blood and spenal markers were higher in in test group vs. control group (∑Gi = 16; ∑Di = 4,38 vs. ∑Gi = 13; ∑Di = 2,28). This phenomenon is probably due to the development adaptive reactions disruption in the immune system and development secondary immunodeficiency states in the offspring of rats.Violations of immunoreactivity, as well as disruption the possibility of operational restructuring of the immune system and choosing the best immune response in the offspring of rats whose perinatal development take place under the effect of antigens T. gondii, persists for a long time – within 60 days of postnatal life.